Réponses

2013-05-23T19:10:15+02:00

1) D = 10x - 2x² - 15 + 3x + (4x² - 12x + 9)

D = -2x² + 13x - 15 + 4x² - 12x + 9

D = -2x² + 4x² + 13x - 12x - 15 + 9

D = 2x² + x - 6

 

2) D = (2x - 3)(5 - x) + (2x - 3)²

D = (2x-3) [(5-x) + (2x-3)]

D = (2x-3) (5-x+2x-3)

D = (2x-3) (x+2)

 

3) (2x - 3)(x + 2) = 2x² + 4x - 3x - 6 = 2x² + x -6.

OU SI C'EST UN PRODUIT NUL : 

 

(2x - 3)(x + 2)=0

2x -3=0 ou x+2=0

2x = 3 ou x = -2

x = 1,5 ou x = -2

 

  • Utilisateur Brainly
2013-05-23T19:11:17+02:00

On donne : D =(2x - 3)(5 - x) + (2x - 3)²

 

1)Factoriser D

D =(2x - 3)(5 - x) + (2x - 3)²

    =(2x-3)(5-x+2x-3)

    =(2x-3)(x+2)

 

2)Developper et reduir

D=(2x-3)(x+2)

   =2x²-3x+4x-6

   =2x²+x-6

 

3)Resoudre l'equation (2x - 3)(x + 2)=0

donc 2x-3=0 ou x+2=0

donc x=1,5 ou x=-2